2016
DOI: 10.1073/pnas.1516686113
|View full text |Cite
|
Sign up to set email alerts
|

Increasing instruction time in school does increase learning

Abstract: Increasing instruction time in school is a central element in the attempts of many governments to improve student learning, but prior research-mainly based on observational data-disputes the effect of this approach and points out the potential negative effects on student behavior. Based on a large-scale, cluster-randomized trial, we find that increasing instruction time increases student learning and that a general increase in instruction time is at least as efficient as an expert-developed, detailed teaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 25 publications
(23 reference statements)
1
31
1
Order By: Relevance
“…Within these research works we find Lavy (2015Lavy ( , 2010 analysing PISA 2006 for over 50 countries. This result was also found by Rivkin and Schiman (2015) for 72 countries in PISA 2009 andAndersen et al (2016) for Denmark. Cattaneo et al (2017) built on Lavy (2015) to analyse the case of Switzerland with data on PISA 2009 and also found that a higher number of hours of instruction would mean better academic results, although they claimed that this effect was lower than they expected.…”
Section: Literature Reviewsupporting
confidence: 79%
“…Within these research works we find Lavy (2015Lavy ( , 2010 analysing PISA 2006 for over 50 countries. This result was also found by Rivkin and Schiman (2015) for 72 countries in PISA 2009 andAndersen et al (2016) for Denmark. Cattaneo et al (2017) built on Lavy (2015) to analyse the case of Switzerland with data on PISA 2009 and also found that a higher number of hours of instruction would mean better academic results, although they claimed that this effect was lower than they expected.…”
Section: Literature Reviewsupporting
confidence: 79%
“…Two recent randomized trials that use the same reading test as the outcome but increased the time that children spent with adults by either increasing the number of lessons per week or having two adults in the classroom (coteachers) found effect sizes of similar magnitude; however, public expenditures were at least twice as high (18,19). This observation supports the efficiency of a growth mindset parental reading intervention-even when implemented in realistic settings without full compliance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, interventions targeted toward specific groups of students may in fact widen the gap, if the intervention is as least as beneficial for the class peers. Evidence from Andersen et al (2016a) suggest that increasing weekly instruction time in Danish may widen the reading gap between students of Danish and non-Western origin by as much as 25%.…”
Section: Figure 6 Average National Test Scores In Reading (Left Panementioning
confidence: 99%